Indoor air quality and dustborne biocontaminants in bedrooms of toddlers in Athens, Greece. (15th April 2020) - Stamatelopoulou, A.; Pyrri, I.; Asimakopoulos, D.N.; Maggos, T.
Abstract: Contaminants of biological origin, such as fungi and bacteria, are ubiquitous inside the residences and especially in bedroom microenvironments. Epidemiological studies have shown that fungal exposure is associated with respiratory and allergic symptoms. Infants and young children comprise a susceptible population to study, since they spend most of their day inside their rooms. A study was undertaken to investigate environmental factors (temperature and relative humidity), indoor pollutants (PM2.5, CO2 ), building characteristics and occupant activities in relation to the spectrum and levels of settled fungi in 25 Greek young's children bedrooms, and to evaluate the fungal qualitative and quantitative composition of houses with and without asthmatic/allergic children. In this context, on-site house inspections to study the Indoor Air Quality (IAQ) in bedrooms of young children below three years of age were conducted in Athens, Greece. Sampling campaigns were conducted over one-week period using Electrostatic Dust Collectors (EDCs) to quantify fungal and bacterial exposure in settled dust and real-time monitoring techniques for environmental parameters (T, RH, CO2, PM2.5 ). The present investigation revealed that the predominant dustborne genus was Cladosporium followed by Alternaria and Aspergillus, and that living in a suburban area, the presence of an attached garage and the presence of a carpet in the bedroom were significant predictors of fungal concentrations. Furthermore, although the difference was not statistically significant, higher fungal concentrations were recorded in the houses with asthmatic or atopic children. Highlights: Fungal and bacterial exposure in settled dust was assessed in bedrooms of young children. The predominant dustborne genus was Cladosporium followed by Alternaria and Aspergillus. Temperature and relative humidity seemed to have little effect in fungal concentrations. Living in a suburban area and the presence of an attached garage a were significant predictors of fungal concentrations. Higher fungal concentrations were recorded in the houses with asthmatic or atopic children.